2006
DOI: 10.1901/jeab.2006.15-05
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Equivalence: Testing Sidman's (2000) Theory

Abstract: Sidman's (2000) theory regarding the origin of equivalence relations predicts that a reinforcing stimulus common to distinct equivalence classes must drop out of the equivalence relations. This prediction was tested in the present study by arranging class-specific reinforcers, R1 and R2, following correct responding on the prerequisite conditional discriminations (Ax-Bx, Cx-Bx) for two stimulus classes, A1B1C1 and A2B2C2. A class-common reinforcer, R3, was presented following correct responding on the prerequi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(61 citation statements)
references
References 30 publications
6
50
0
5
Order By: Relevance
“…Porém, os resultados obtidos nas tentativas de sonda AB, BA, AC, CA, BC e CB mostraram que as classes de equivalência A1B1C1, A2B2C2 e A3B3C3 não foram estabelecidas a partir do treino em MTS de identidade com as consequências específicas empregadas no Experimento 1. Esses dados contradizem praticamente todos os resultados apresentados em estudos prévios nos quais relações condicionais arbitrárias emergiram a partir de um treino com características semelhantes (Dube & McIlvane, 1995;Dube et al, 1987;Dube et al, 1989;Goyos, 2000;Joseph et al, 1997;Johnson et al, 2014;Minster et al, 2006;Schenk, 1994;Varella & de Souza, 2014).…”
Section: Discussionunclassified
“…Porém, os resultados obtidos nas tentativas de sonda AB, BA, AC, CA, BC e CB mostraram que as classes de equivalência A1B1C1, A2B2C2 e A3B3C3 não foram estabelecidas a partir do treino em MTS de identidade com as consequências específicas empregadas no Experimento 1. Esses dados contradizem praticamente todos os resultados apresentados em estudos prévios nos quais relações condicionais arbitrárias emergiram a partir de um treino com características semelhantes (Dube & McIlvane, 1995;Dube et al, 1987;Dube et al, 1989;Goyos, 2000;Joseph et al, 1997;Johnson et al, 2014;Minster et al, 2006;Schenk, 1994;Varella & de Souza, 2014).…”
Section: Discussionunclassified
“…That is, they mean the same thing and can be used interchangeably by a mature English speaker and reader. Earlier, we discussed that, to date, several studies have demonstrated the effectiveness of the differential outcomes training procedure in facilitating the acquisition of equivalence stimulus relations across different individuals, ranging from individuals with mental retardation (e.g., Dube & McIlvane, 1995) to typical young adults (Minster et al, 2006;see Tables 1 and 2).…”
Section: The Do Procedures As a Training And Pedagogical Toolmentioning
confidence: 99%
“…Positive results have been yielded in such diverse populations as youngsters with mental retardation (ages 13-21 years; Dube & McIlvane, 1995), adults with Prader-Willi syndrome (Joseph, Overmier, & Thompson, 1997), typical preschool children (Goyos, 2000;Schenk, 1994), and, more recently, typical young adults as well (Minster, Jones, Elliffe, & Muthukumaraswamy, 2006).…”
Section: Experimental Evidence In Humansmentioning
confidence: 99%
See 2 more Smart Citations